Life style as a measure of socio-economic status: The development of an instrument for use in Jamaica - Leo-Rhynie, Elsa
Researchers in Jamaica involved in determining socio-economic status (SES) generally employ a single index (i.e., Occupational Level) for this purpose. Recognition of the shortcomings of such a measure has resulted in the construction of a more comprehensive instrument, which attempts to tap numerous indices of SES, termed a Life Style Scale. This paper reports on the stages involved in establishing construct validity and reliability for the final 44-item form of the scale, and suggests as well, that a short-form version of 23 items is equally reliable and valid in terms of its use in determining lifestyle
Keywords: Life styles